Развитие креативности учащихся и студентов как образовательная стратегия современной системы образования - Малахова, Ирина А. (International dialogues on education, 2016)
The article investigates problems with the development of creativity. It describes the main lines of creativity research, and analyzes existing scientific approaches to the study of this phenomenon: naive, contemplative, monodisciplinary and interdisciplinary. The paper presents the author’s interpretation of the essence of creativity and its structure, shows the dual nature of creativity as a personal quality, including indicators of creativity and behavioral forms of its manifestation. Based on a wide range of scientific sources the history and current state of the development of creativity are analyzed. The nature and structure of creativity, developmental stages of the creative person, creation and creativity, diagnosis of creativity as a scientific problem, age-related specifics of creativity are outlined. This article focuses on the scientific design and justification of the need for a creative educational environment for pupils and students to foster their creativity as an integrative personal property. Based on the study, the author shows the age characteristics of the development of creativity of pupils and students, levels of development and pedagogical tasks in support of this process in cultural and continuing-educational institutions.